Sulfur-based glass-ceramic solid electrolyte and preparation method thereof
By introducing the A components in the sulfide solid electrolytes to form a glass network, the problem of low critical current density of solid electrolytes in the existing sulfide is solved. Reduce cost and energy consumption.
Patent Information
- Application Number
- CN202211553256.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-06
AI Technical Summary
The critical current density of existing sulfide solid electrolytes is low, which causes the battery to easily cause dendrite growth under high current density, resulting in short circuits and failures, and cannot meet the requirements of large-scale energy storage batteries.
Using a chalcogenide glass ceramic solid electrolyte, its composition is xLi2S-yP2S5-zASm, which is formed by introducing the A component (such as elements in B, Al, Ga, In, Si, Sn, Ge, As, Sb, Bi and Mo) Glass network, improves density and inhibits dendrite growth.
It achieves high room temperature critical current density and ionic conductivity, extends the cycle life of the battery, reduces cost and energy consumption, and is compatible with high-voltage cathode materials.
Smart Images

Figure CN115947542B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid electrolytes, and in particular relates to a sulfur-based glass ceramic solid electrolyte and a preparation method thereof. Background Art
[0002] With the growing demand for electrification of transportation in modern society, there is an urgent need to develop energy storage devices with high power density, high safety and long cycle life. Replacing the toxic and flammable organic electrolytes in commercial lithium-ion batteries with solid electrolytes is considered to be the best strategy to break through the energy density and safety limitations of existing batteries. At present, sulfide solid electrolytes have high ionic conductivity, are easy to deform at room temperature and have good processing performance, which is convenient for large-scale industrial production. They are regarded as the solid electrolyte materials with the most application potential. The properties of the solid electrolyte itself are one of the main factors affecting its critical current density. At present, the critical current density of sulfide solid electrolytes is low. At a higher current density, it will cause dendrite growth, leading to problems such as short circuit and failure in the battery. This greatly limits the power density and cycle life of the battery, making it difficult to achieve rapid charging and discharging at a higher current density, and cannot meet the requirements of current electric vehicle power batteries and large-scale energy storage batteries.
[0003] Based on Li 2 SP 2 S 5 The sulfide solid electrolyte of the system is the most common sulfide solid electrolyte at present. It also has the problem of low critical current density. Although its ionic conductivity is relatively high, its ionic conductivity is limited by the raw materials and preparation process. In order to obtain relatively high ionic conductivity, it is often necessary to use more expensive raw materials with small reserves and scarce resources and use a longer high-temperature treatment time, which has high cost and energy consumption, and will sacrifice other properties such as material stability, resulting in poor overall performance of the material. The main reasons for the low critical current density of existing sulfide solid electrolytes include the Li-based 2 SP 2 S 5 The sulfide solid electrolyte of the system, including the sulfide solid electrolyte itself, has a limited electrochemical stability window. When it comes into contact with metallic lithium, it will generate an interface layer of mixed ion-electron conductivity. This interface layer cannot prevent the continuous decomposition of the sulfide solid electrolyte, and induces the continuous growth of lithium dendrites in the sulfide solid electrolyte, and ultimately leads to a short circuit in the battery.
[0004] At present, there are two main methods for preparing sulfide solid electrolytes. One is the commonly used high-energy ball milling method. The microstructure of the solid electrolyte prepared by this method is not dense enough and cannot effectively inhibit the growth of dendrites. The other is the high-temperature melting method. Although this method can improve the density of the solid electrolyte, its high-temperature treatment time is long (>10 hours), the energy consumption is high, and the raw material Li is not dense enough at high temperature. 2S corrosion to the reaction vessel prevents the addition of too much Li 2 S limits the molar percentage of lithium ions, thus hindering the further improvement of the ionic conductivity and comprehensive performance of the solid electrolyte. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a sulfur-based glass-ceramic solid electrolyte and a preparation method thereof in view of the deficiencies in the prior art. The solid electrolyte has high room temperature critical current density, high room temperature ionic conductivity, short high temperature treatment time, good mechanical properties, high oxidation resistance potential, low cost and energy consumption, and good comprehensive performance, and can solve the problems of limited power density and cycle life of all-solid-state batteries.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a sulfur-based glass ceramic solid electrolyte, whose composition formula is xLi 2 S-Y 2 S 5 -zAS m , wherein x, y, and z are all molar ratios, 0.5≤x≤0.8, 0.05≤y≤0.3, 0.02≤z≤0.3, and x / (x+y+z)>0.5, the value of m is 1, 1.5 or 2, and A is at least one element selected from B, Al, Ga, In, Si, Sn, Ge, As, Sb, Bi and Mo.
[0007] The chalcogenide glass ceramic solid electrolyte of the present invention uses at least one element of B, Al, Ga, In, Si, Sn, Ge, As, Sb, Bi and Mo as component A. The introduction of component A is not only conducive to the improvement of ionic conductivity, but more importantly, A, as a glass network former, can effectively improve the density of the chalcogenide glass ceramic solid electrolyte, which is conducive to inhibiting dendrite growth and improving its critical current density.
[0008] The ionic conductivity of the sulfur-based glass ceramic solid electrolyte at room temperature is (1-4)×10 -3 S / cm, and has a very high room temperature critical current density of 1 to 1.7 mA / cm 2 In practical applications of batteries, the charge and discharge current can be 0.3 mA / cm 2 The device can run stably for more than 400 hours. This is because the interface layer generated by the sulfur-based glass ceramic solid electrolyte of the present invention when in contact with lithium metal has poor electronic conductivity, and the interface layer can effectively avoid problems such as dendrite growth and short circuit caused by electron percolation.
[0009] The inventors of the present application unexpectedly discovered that: 1) the sulfur-based glass-ceramic solid electrolyte of the present invention exhibits a maximum ionic conductivity at different A component contents, the structural cause of which is the mixed glass network former effect; 2) the sulfur-based glass-ceramic solid electrolyte of the present invention has a long cycle life.
[0010] The sulfide glass ceramic solid electrolyte of the present invention is not a completely amorphous structure, but a β-Li 3 PS 4 X-ray diffraction signal. It is precisely because the sulfur-based glass-ceramic solid electrolyte of the present invention is a glass-ceramic structure of high-conductivity nanocrystals wrapped in a glass matrix that the solid electrolyte not only has high conductivity, but is also easy to deform, can be cold-pressed at room temperature and has high density, and has good mechanical strength due to the appearance of crystals. These two aspects have the following advantages: 1) The sulfur-based glass-ceramic solid electrolyte of the present invention has high ionic conductivity and has a small internal resistance when assembled into an all-solid-state battery;
[0011] 2) High density and good mechanical strength are conducive to dendrite suppression, which is crucial for maintaining the electron blocking and ion conductivity of the solid electrolyte. Therefore, all-solid-state batteries using such solid electrolytes can have a long cycle life.
[0012] Preferably, A is at least one element selected from the group consisting of B, Al, Si, Sn, Sb and Mo.
[0013] The preparation method of the above-mentioned chalcogenide glass ceramic solid electrolyte comprises the following steps:
[0014] (1) The raw material Li 2 S.P. 2 S 5 ,AS m The powders are weighed and mixed according to the proportion, and high-energy ball milling is performed at a rotation speed of 200 to 800 rpm for 10 to 40 hours to allow the raw materials to fully react to form a uniform precursor;
[0015] (2) Heat the precursor until it is molten and keep it warm for 0.5 to 5 hours, with a temperature greater than 10 3 The sulfide glass ceramic solid electrolyte xLi was obtained by cooling to room temperature at a cooling rate of 100 °C / min. 2 S-Y 2 S 5 -zAS m .
[0016] The inventors of the present application also unexpectedly discovered that the melting treatment time of the sulfur-based glass-ceramic solid electrolyte of the present invention is 0.5 to 5 hours, and when the sulfur-based glass-ceramic solid electrolyte is prepared by the preparation method of the present invention, the reaction can be completed at a relatively low temperature (<1000° C.).
[0017] The preparation method of the sulfur-based glass-ceramic solid electrolyte of the present invention first uses a high-energy ball milling method to convert the raw materials into a uniform precursor, and then performs a high-temperature melting treatment on the precursor to make it densified. At the same time, since the raw materials have undergone a certain reaction during the high-energy ball milling process, the time of the high-temperature melting treatment can be greatly shortened to 0.5 to 5 hours. While reducing costs and energy consumption, the corrosion of the raw materials to the reaction vessel and the introduction of corresponding impurities can be effectively reduced, that is, a higher molar proportion of Li (that is, x / (x+y+z)>0.5) is achieved without introducing impurities, and a higher molar proportion of Li can provide a higher carrier concentration, which is conducive to achieving a higher ionic conductivity.
[0018] Preferably, in step (1), the rotation speed of the high-energy ball mill is 400 to 700 rpm, and the high-energy ball milling time is 10 to 20 hours.
[0019] Preferably, in step (2), the precursor is heated to 700-1000° C. and kept at this temperature for 0.5-5 hours.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. High room temperature ionic conductivity: The room temperature ionic conductivity of the sulfur-based glass ceramic solid electrolyte of the present invention is in the range of (1 to 4)×10 -3 S / cm, which is close to the conductivity of commercial liquid organic electrolytes, making the sulfur-based glass-ceramic solid electrolyte of the present invention extremely advantageous in the application of high-rate all-solid-state batteries;
[0022] 2. High critical current density at room temperature: The critical current density of the sulfur-based glass ceramic solid electrolyte of the present invention is 1.2-1.7 mA / cm 2 This is because the sulfide glass ceramic solid electrolyte of the present invention is not only conducive to inhibiting the growth of dendrites in terms of composition, but also has a denser structure and fewer surface defects after high-temperature melting treatment, thereby effectively eliminating the growth sites of dendrites, thereby achieving a higher critical current density;
[0023] 3. Short high-temperature treatment time: Thanks to the fact that the raw materials are fully reacted by high-energy ball milling to generate a uniform precursor before high-temperature melting treatment, the high-temperature melting treatment time during the preparation of the sulfur-based glass-ceramic solid electrolyte of the present invention is shortened to 0.5 to 5 hours, thereby saving a large amount of energy in the preparation process, and also avoiding the side reaction between the raw materials and the reaction vessel and the introduction of impurities, thereby ensuring the high critical current density and high ionic conductivity of the electrolyte; the sulfur-based glass-ceramic solid electrolyte prepared by the preparation method of the present invention has a dense structure, few impurities, and low electronic conductivity, thereby achieving a high critical current density, thereby avoiding the dendrite growth and subsequent internal short circuit problems caused by the components of the all-solid-state battery, and solving the problem of limited power density and cycle life of the all-solid-state battery;
[0024] 4. Good mechanical properties: The sulfur-based glass-ceramic solid electrolyte of the present invention has a relatively dense structure, and has flexibility and suitable mechanical properties. On the one hand, the solid electrolyte of the present invention can form high-quality interface contact with the electrode by direct pressurization, and is compatible with the sulfide solid electrolyte battery assembly process; on the other hand, the good mechanical properties can effectively inhibit the growth of dendrites;
[0025] 5. High oxidation resistance potential: The oxidation resistance potential of the sulfur-based glass-ceramic solid electrolyte of the present invention is 4.5V, with strong oxidation resistance and no obvious space charge layer, and is compatible with high-voltage positive electrode materials; the sulfur-based glass-ceramic solid electrolyte of the present invention can withstand high voltages up to 4.5V, and is compatible with existing mainstream lithium battery positive electrode materials (lithium cobalt oxide, ternary materials and lithium iron phosphate, etc.), and such positive electrode materials can be used without coating, and there is no obvious impedance increase when high-voltage electrode materials come into contact with such electrolytes, indicating that no obvious space charge layer is generated when the sulfur-based glass-ceramic solid electrolyte of the present invention comes into contact with high-voltage positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Nyquist plot of the chalcogenide glass ceramic solid electrolyte prepared in Example 1;
[0027] Figure 2 The XRD crystal diffraction data diagram of the chalcogenide glass ceramic solid electrolyte prepared in Example 1;
[0028] Figure 3 This is a critical current density data diagram of the chalcogenide glass ceramic solid electrolyte prepared in Example 1;
[0029] Figure 4 This is a surface morphology of the precursor of the chalcogenide glass ceramic solid electrolyte prepared in Example 1;
[0030] Figure 5 This is a surface morphology of the sulfur-based glass-ceramic solid electrolyte prepared in Example 1. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below with reference to the accompanying drawings.
[0032] Example 1: 0.8Li 2 S-0.05P 2 S 5 -0.3Sb 2 S 3 Preparation of Chalcogenide Glass-ceramic Solid Electrolyte
[0033] Directly 2 S.P. 2 S 5 , Sb 2 S 3 The powders were weighed and mixed according to the proportion, and high-energy ball was carried out at a speed of 400 rpm for 20 hours to allow the raw materials to fully react to form a uniform precursor; then the precursor was heated to 900 ° C for 5 hours to melt, and the temperature was kept at more than 10 3 The sulfide glass ceramic solid electrolyte 0.8Li was obtained by cooling to room temperature at a cooling rate of 1.5 °C / min. 2 S-0.05P 2 S 5 -0.3Sb 2 S 3 The entire preparation process is carried out under the protection of an inert atmosphere to prevent the raw materials from reacting with air.
[0034] After measurement, the 0.8Li prepared in Example 1 2 S-0.05P 2 S 5 -0.3Sb 2 S 3 Sulfur-based glass-ceramic solid electrolytes have the following properties:
[0035] Room temperature ionic conductivity (30°C): 1.4×10 -3 S / cm;
[0036] Oxidation resistance potential: 4.5V;
[0037] Room temperature critical current density (30°C): 1.7 mA / cm 2 ;
[0038] Mechanical properties: Glass-ceramic state, with flexibility and suitable mechanical properties. A complete and smooth solid electrolyte sheet with a thickness of about 0.5 mm can be obtained under a pressure of 100 MPa at room temperature.
[0039] 0.8Li prepared in Example 1 2 S-0.05P 2 S 5-0.3Sb 2 S 3 The ionic conductivity of the chalcogenide glass-ceramic solid electrolyte is 1.4×10 -3 S / cm(see Figure 1 ), which has a glass ceramic structure (see Figure 2 ), the critical current density at room temperature is 1.7 mA / cm 2 (See Figure 3 ), and the solid electrolyte precursor has many surface defects and holes (see Figure 4 ), while the surface of the sulfide glass ceramic solid electrolyte is smooth after high temperature treatment (see Figure 5 ). This proves that the precipitation of high-conductivity crystals and the improvement of ion transport paths are the main factors for its high ion conductivity, and its composition and surface structure are conducive to improving the critical current density of the sulfide glass-ceramic solid electrolyte at room temperature, that is, effectively inhibiting the growth of dendrites, solving the problems of limited power density and internal short circuit of all-solid-state batteries based on all-solid-state battery electrolytes, so that all-solid-state batteries can also have higher power density and longer cycle life.
[0040] Example 2: 0.5Li 2 S-0.1P 2 S 5 -0.3B 2 S 3 Preparation of Chalcogenide Glass-ceramic Solid Electrolyte
[0041] Directly 2 S.P. 2 S 5 , B 2 S 3 The powders were weighed and mixed according to the proportion, and high-energy ball was carried out at a speed of 500 rpm for 15 hours to allow the raw materials to fully react to form a uniform precursor; then the precursor was heated to 800 ° C for 0.5 hours to melt, and the temperature was kept at more than 10 3 The sulfide glass ceramic solid electrolyte 0.5Li 2 S-0.1P 2 S 5 -0.3B 2 S 3 The entire preparation process is carried out under the protection of an inert atmosphere to prevent the raw materials from reacting with air.
[0042] After measurement, the 0.5Li prepared in Example 2 2 S-0.1P 2 S 5 -0.3B 2 S 3 Sulfur-based glass-ceramic solid electrolytes have the following properties:
[0043] Room temperature ionic conductivity (30°C): 1.4×10 -3 S / cm;
[0044] Oxidation resistance potential: 4.5V;
[0045] Room temperature critical current density (30°C): 1.5 mA / cm 2 ;
[0046] Mechanical properties: Glass-ceramic state, with flexibility and suitable mechanical properties. A complete and smooth solid electrolyte sheet with a thickness of about 0.5 mm can be obtained under a pressure of 100 MPa at room temperature.
[0047] Example 3: 0.7Li 2 S-0.3P 2 S 5 -0.05SiS 2 Preparation of Chalcogenide Glass-ceramic Solid Electrolyte
[0048] Directly 2 S.P. 2 S 5 、SiS 2 The powders were weighed and mixed according to the proportion, and high-energy ball was carried out at a speed of 700 rpm for 10 hours to allow the raw materials to fully react to form a uniform precursor; then the precursor was heated to 700 ° C to melt and kept warm for 1 hour, and the temperature was greater than 10 3 The sulfide glass ceramic solid electrolyte 0.7Li was obtained by cooling to room temperature at a cooling rate of 1.5 °C / min. 2 S-0.3P 2 S 5 -0.05SiS 2 The entire preparation process is carried out under the protection of an inert atmosphere to prevent the raw materials from reacting with air.
[0049] After measurement, the 0.7Li prepared in Example 3 2 S-0.3P 2 S 5 -0.05SiS 2 Sulfur-based glass-ceramic solid electrolytes have the following properties:
[0050] Room temperature ionic conductivity (30°C): 3.5×10 -3 S / cm;
[0051] Oxidation resistance potential: 4.5V;
[0052] Room temperature critical current density (30°C): 1.2 mA / cm 2 ;
[0053] Mechanical properties: Glass-ceramic state, with flexibility and suitable mechanical properties. A complete and smooth solid electrolyte sheet with a thickness of about 0.5 mm can be obtained under a pressure of 100 MPa at room temperature.
[0054] Example 4: 0.6Li 2 S-0.15P 2 S 5 -0.08MoS 2 Preparation of Chalcogenide Glass-ceramic Solid Electrolyte
[0055] Directly 2 S.P. 2 S 5 、MoS 2 The powders were weighed and mixed according to the proportion, and high-energy ball was carried out at a speed of 600 rpm for 20 hours to allow the raw materials to fully react to form a uniform precursor; then the precursor was heated to 800 ° C for 2 hours to melt and keep warm for more than 10 3 The sulfide glass ceramic solid electrolyte 0.6Li was obtained by cooling to room temperature at a cooling rate of 1.5 °C / min. 2 S-0.15P 2 S 5 -0.08MoS 2 The entire preparation process is carried out under the protection of an inert atmosphere to prevent the raw materials from reacting with air.
[0056] After measurement, the 0.6Li prepared in Example 4 2 S-0.15P 2 S 5 -0.08MoS 2 Sulfur-based glass-ceramic solid electrolytes have the following properties:
[0057] Room temperature ionic conductivity (30°C): 2.2×10 -3 S / cm;
[0058] Oxidation resistance potential: 4.5V;
[0059] Room temperature critical current density (30°C): 1.3 mA / cm 2 ;
[0060] Mechanical properties: Glass-ceramic state, with flexibility and suitable mechanical properties. A complete and smooth solid electrolyte sheet with a thickness of about 0.5 mm can be obtained under a pressure of 100 MPa at room temperature.
Claims
1. A chalcogenide glass ceramic solid electrolyte, characterized in that: Its composition formula is xLi2S-yP2S5-zAS m , wherein x, y, and z are all molar ratios, 0.5≤x≤0.8, 0.05≤y≤0.3, 0.02≤z≤0.3, and x / (x+y+z)>0.5, m is 1, 1.5 or 2, A is at least one element selected from B, Al, Ga, In, Si, Sn, Ge, As, Sb, Bi and Mo, and the preparation method thereof comprises the following steps: (1) Raw materials Li2S, P2S5, AS m The powders are weighed and mixed according to the proportion, and high-energy ball milling is performed at a rotation speed of 200-800 rpm for 10-40 hours to allow the raw materials to fully react to form a uniform precursor; (2) Heat the precursor to 700~1000℃ and melt it and keep it warm for 0.5~5 hours. 3 The sulfide glass ceramic solid electrolyte xLi2S-yP2S5-zAS was obtained by cooling to room temperature at a cooling rate of 100 °C / min. m .
2. The chalcogenide glass ceramic solid electrolyte according to claim 1, characterized in that: A is at least one element selected from the group consisting of B, Al, Si, Sn, Sb, and Mo.
3. The chalcogenide glass ceramic solid electrolyte according to claim 1, characterized in that: In step (1), the rotation speed of the high energy ball mill is 400-700 rpm, and the high energy ball milling time is 10-20 hours.
Citation Information
Patent Citations
Manufacturing method of lithium ion conductive material
JP2012043654A
Glass ceramic
JP2013116837A
Sulfide solid electrolyte material, cell and method of producing sulfide solid electrolyte material
JP2015032550A
Li2S-P2S5-B2S3 glass ceramic and all-solid-state secondary battery
KR1020190132965A